Semantic Analysis on the Malay Islamic Concept of Man and Universe - Othman, Hussain (Journal of Islam in Asia (E-ISSN 2289-8077), 2010)
What was the true concept of man and universe as understood by the Malay Muslims and depicted by their classical texts? Oftentimes, the Hindu concept of devaraja or kingship and the concept of mount Mahameru were seen as the most appropriate Malay concept of man and universe. Unfortunately, these two concepts representing only a minor part of the Malay classical tradition. Other dominant part of the Malay intellectual legacy, i.e. the Malay Islamic tradition was frequently neglected. Obviously, it is not so easy to describe the concept of man and universe in Malay Islamic tradition due to the limitation of sources and proper approaches to be employed. Studies however showed that a proper understanding upon the worldviews of the past could be possible if we choose to look through the eyes of the people of the time. Based on this notion, this study has selected the semantic approach to unveil a proper Malay Islamic concept of man and universe. The approach was well known to us through the writings of a Japanese scholar, Toshihiko Izutsu. Semantic, according to Izutsu is an analytic study of the key-terms of a language with a view arriving eventually at a conceptual grasp of the weltanschauung or world-view of the people. Through this approach, the study has finally arrived at the conclusion that the Malay Islamic concept of man is not the concept of the devaraja or “kingship”, rather it was strongly based on the concept of duties and responsibilities inspired by the religious consciousness of the people. Similarly, the Malay Islamic concept of universe is not the concept of mount Mahameru. It was rather the concept of al-dunya wal akhirah. The purpose of this paper is to discuss further some tremendous discoveries of the Malay Islamic concept of man and universe embedded in three great books of Malay history namely Sejarah Melayu, Hikayat Raja-raja Pasai and Hikayat Merong Mahawangsa.